Modern blood banking and transfusion practices - F.A. Davis Company (Philadelphia : F.A. Davis Company, 2005)
Contents: Red cell and platelet preservation: historical perspectives, review of metabolism, and current trends -- Basic genetics for blood bankers -- Fundamentals of immunology for blood bankers -- Concepts in molecular biology -- The antiglobulin test -- The ABO blood group system -- The RH blood group system -- The Lewis system and the biological significance -- Other major blood group systems -- The red cell surface antigen terminology and miscellaneous blood groups donor screening and component preparation -- Donor screening and component preparation -- Detection and identification of antibodies -- Pretransfusion compatibility testing -- Orientation to the modern blood bank laboratory -- Alternative technologies and automation in routine blood bank testing -- Transfusion therapy and transfusion in transplantation -- Apheresis -- Adverse effects of blood transfusion -- Transfusion-transmitted diseases -- Hemolytic disease of the newborn and fetus -- Autoimmune hemolytic anemias -- The HLA system -- Parentage testing -- Quality management in the blood bank -- Transfusion safety and federal regulatory requirements -- Informational systems in the blood bank -- Medicolegal and ethical aspects of providing blood collection and transfusion services.
Includes bibliographical references and index.
Keywords: Blood banks; Blood -- Transfusion; Immunohematology; Blood Banks -- methods; Blood Grouping and Crossmatching; Blood Transfusion -- methods